Transnational review on the use of information and communication technologies and technoscience in healthcare: Their impact on the autonomy and governance of individuals and communities. - Unanue Cuesta, Concepción (Bioethics, 2025)
The impact and use of Information and Communication Technologies (ICTs) in healthcare settings has been increasing since 2019. This is greatly due to the COVID‐19 pandemic. But beyond accommodating an extraordinary and complex situation in terms of healthcare services, or beyond replacing personalised care delivered by healthcare professionals (HCPs), has there been a process of information and consultation for communities and HCPs? Do we have the basic requirements needed to make such use commonplace in health care? What will the impact be on communities and their governance? Have we arrived here by consensus or by imposition? Our purpose has been to conduct a transnational analysis by approaching communities, social actors, and healthcare professionals in three territories in a pilot study following a qualitative methodology. The aim being to discover the potential impact of such measures beyond the right to health and if such measures are compatible with the purpose of population settling in rural areas. Furthermore, to identify if this entails a conflict of value and priorities or if we need new ethical reviews both for communities and healthcare professionals.